Perkembangan Populasi Empoasca sp. (Homoptera : Cicadelidae) di Kebun Teh Pagilaran - Pachrudin Pachrudin; Witjaksono Witjaksono; Arman Wijonarko (Jurnal Perlindungan Tanaman Indonesia, 2007)
Empoasca sp. was first reported as pest in West Java tea plantation in 1998. In 2000, this cicadellid was also found in Pagilaran tea plantation in Central Java. The aim of this research was to observe the preferences of Empoasca sp. to tea cultivars and the effect of altitude and climate factors to population dynamics of Empoasca sp. the result showed that Kiara 8 cultivar planted in 700 - 850 m asl was highly susceptible to Empoasca sp. The lowest population and the least damage was found in PS 1 cultivar which has leaves with the densest hair. Intensity of the rain-fall was likely to have higher impact to population of Empoasca sp. rather than humidity and temperature.